PENGEMBANGAN POTENSI YANG TERDAPAT DI DESA WISATA KREBET SEBAGAI DAYA TARIK WISATA DI KABUPATEN BANTUL - , FENDI APRIYADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tourism village has developed into the one of some destinations that demanded by tourist or traveler. The appearance of the tourism village is caused by potential tourism which can be managed to be tourism attraction. In this observation, the tourism village that uses as an object is which there are batik-work with wood as its median to be towing tourist. Krebet Tourism Village is located in Sendangsari Village, Pajangan Sub-district, Bantul Distrik, Yogyakarta. The existences of Krebet Tourism Village gives a lot benefits to the local people, so the expansion of potential tourism in this area is needed so then the positive benefits of it can be feel by the local people as the business rooms. The observation method of qualitative analysis descriptive is where the researcher depict the phenomenon with analyse and present the facts in systematic way to make easy in understanding and make conclusions. The result from the observation can be concluded that beside of batik art work with wood median, the potential and tourism attraction which Krebet Tourism Village has are natural tourism and culture, just like Jurang Pulosari, Bercocok Tanam, Jelajah Desa, Merti Dusun, Membatik, Mengukir, etc. The conclusion from the study about Krebet Tourism Village is the expansion of the tourism potential in Krebet Tourism Village really need to increase the tourism visit. Krebet Tourism village still has many spaces to grow and compete in tourism at Yogyakarta, especially Bantul.